Scientific Foundations for Preparing Future Teachers for Active Communication in a Cultural Environment - Muzropova Guljamol Mardonovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: The article explores the scientific foundations for preparing future teachers to engage in active communication within a cultural environment. The study analyzes pedagogical approaches, didactic methods, and theoretical concepts that contribute to the development of intercultural communication skills in future educators. Emphasis is placed on the role of scientific principles in fostering students’ social and cultural competence, enhancing their ability to interact effectively in diverse cultural settings, and promoting active participation in educational and social communication processes.